Investigation of factors affecting the shuttle speed in football - Temur, H. B.; Gülesce, M. (International Journal of Applied Exercise Physiology, 2019)
In this study, it was aimed to investigate whether age, body weight, upper stroke training, leg strength and waist force affect the smoothing speed in the individuals who received football training. With the aim of this study, the average age of 12.89 ±, 80 years, which is operating in the province of Van, Besiktas football school (23) and Basaksehir football school (15) a total of 38 male individuals were included in the study with the consent of their parents. In both football schools, the height, body weight, leg strength, waist force and shooting speed of the athletes were measured before the training started. Then, in the two football schools, the same training program was applied for two weeks, two days a week for 12 weeks. However, athletes trained in Besiktas football school were given extra strokes training for 12 weeks. At the end of this period, the measurements taken before the training program were repeated. Data were analyzed by using Paired Samples, Anova and Correlation methods in SPSS 21 package program. As a result of the analyzes, it was determined that there was a significant increase (p <0.01) between the pretest and post-test values of body weight, leg strength, waist force and smash speed of Besiktas football school athletes. When the same variables were examined in Basaksehir football school athletes, there was a significant increase in p <0.01 level between the pre-test and post-test values of the variables except waist force and smash velocity. A significant decrease (p <0.01) was observed in the shot speed. Again, there was no significant difference between the waist and leg strengths of the two groups in terms of the differences between the pre-test and post-test values, and the difference in p-0.01 was found to be different in favor of Besiktas football school. In the correlation analysis, both pre-test and post-test values were found to be positively related to waist and leg strength in terms of smash speed. As a result, it can be said that the impact of the technical training is more effective as the waist and leg strength of the given upper stroke training positively affects the smash speed.